Developing a Classroom Teaching Quality Evaluation Index System in the Context of Digital Transformation: Based on Delphi and AHP - Rongxia Hao; Amando Yutuc (International Journal of Instructional Technology and Educational Studies)
Amid the wave of digital transformation, classroom teaching in universities is experiencing innovations in educational concepts, teaching methods, and learning styles. To adapt to these changes, the traditional evaluation index system for classroom teaching quality urgently needs updating. This study aimed to construct an evaluation index system for classroom teaching quality that meets the requirements of digital transformation, thereby enhancing the scientific and effective nature of evaluations. By comprehensively utilizing literature review, policy analysis, and specialized group discussions, a preliminary evaluation index questionnaire was drafted. The Delphi method was then employed, inviting experts in the field to evaluate and revise the questionnaire items. After two rounds of expert consultations, an evaluation system including 6 primary indicators and 32 secondary indicators was established. The Analytic Hierarchy Process (AHP) was used to determine the weight of each indicator, ensuring the validity and effectiveness of the evaluation system. This system had received high recognition from the experts, indicating a high level of consensus, and demonstrating excellent scientific reliability. The findings from this study not only shed light on the practice of teaching quality evaluation but also paved the way for reforming classroom teaching at universities.